THE IMPACT OF MEDIA LITERACY ON THE DEVELOPMENT OF SPEECH SKILLS: A COMPREHENSIVE ANALYSIS - Hilola Nadirova-Kazan (Next Scientists Conferences, 2023)
This thesis explores the intricate relationship between media literacy and the development of speech skills, shedding light on the profound influence that media consumption has on individuals' ability to communicate effectively. As society becomes increasingly interconnected through various media platforms, the role of media literacy in shaping speech skills gains paramount importance. The study delves into the multifaceted aspects of media literacy, examining how exposure to diverse forms of media can either enhance or impede the acquisition and refinement of speech skills. Through a synthesis of existing research and original insights, this thesis aims to provide a comprehensive understanding of the mechanisms underlying the development of speech skills in the context of media literacy.